2018
DOI: 10.1080/09593985.2017.1423142
|View full text |Cite
|
Sign up to set email alerts
|

Can pain beliefs change in middle school students? A study of the effectiveness of pain neuroscience education

Abstract: Pain neuroscience education (PNE) is an educational strategy aimed at teaching people more about pain from a neurobiological and neurophysiological perspective. Current best-evidence provides strong support for PNE to positively influence pain ratings, dysfunctions, fear-avoidance and pain catastrophization, limitations in movement, pain knowledge, and healthcare utilization. To date, all PNE studies have been conducted on adult populations. This study set out to explore if an abbreviated PNE lecture to middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(88 citation statements)
references
References 51 publications
6
79
0
3
Order By: Relevance
“…17,18 There is limited evidence investigating pain science education in adolescents. To date, three school-based studies have demonstrated that adolescents have the capacity to learn pain science topics via a 30-minute lecture, 19 an 11-minute video, 20 and a four-week classroom-style intervention. 21 The classroom intervention study is the only randomized controlled trial, investigating the effects of adolescent pain science education, by combining education with neck exercises for chronic neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 There is limited evidence investigating pain science education in adolescents. To date, three school-based studies have demonstrated that adolescents have the capacity to learn pain science topics via a 30-minute lecture, 19 an 11-minute video, 20 and a four-week classroom-style intervention. 21 The classroom intervention study is the only randomized controlled trial, investigating the effects of adolescent pain science education, by combining education with neck exercises for chronic neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 25% of individuals under the age of 19 have experienced pain in the last three months, with "intense and frequent" pain being reported in 6-8% of all children [1,2]. Furthermore, 92.5% of middle school students reported knowing someone living with persistent pain [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the food and drug administration (FDA) published guidelines for dosing of extended release oxycodone for children as young as eleven years old [7]. The need for effective treatment of pediatric pain is self-evident: children in pain can become adults in pain, risking a staggering emotional, economic and societal burden [3,8,9]. These adolescent and child statistics pertaining to pain and opioid exposure/use are part of the current pain and opioid epidemic in the United States (US) and globally [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations